Come hell or high water : feminism and the legacy of armed conflict in Central America - Destrooper, Tine (Studies in critical social sciences, 2014)
In Come Hell or High water: Feminism and the Legacy of Armed Conflict in Central America, Tine Destrooper explores the motivations, strategies and priorities of women's activists in Guatemala and Nicaragua. She explains how these priorities were shaped by the legacy of armed conflict and the presence of international aid agencies.